Does Test Difficulty Matter? : Examining the Influence of Stimulus Difficulty on Cues That Affect Learning Confidence in Young Adults - Small, Tyler; Lee, Yan Lin (My University, 2015)
In the current research, we investigated the relative impact of the above-listed cues on subsequent JOL formation as a function of stimulus difficulty. Although difficulty level is widely-used as a manipulation in cognitive research, this is not the case for studies examining JOL formation. Most prior JOL research used word pairs that were homogenous in their difficulty level. We hypothesized that the relative impact of metacognitive cues on JOL formation would differ as a function of stimulus difficulty level (easy vs. hard).
Color poster with text and tables.
Keywords: Memory for past test performance (MPT); Test performance; Judgment of learning (JOL); Posters